2020
DOI: 10.4103/jfmpc.jfmpc_214_19
|View full text |Cite
|
Sign up to set email alerts
|

Acute undifferentiated febrile illness: Protocol in emergency department

Abstract: Fever accounts for around 15% of emergency visits in elderly age group and around 5% in adults. The spectrum of etiologies ranges from non-infectious to infectious etiologies. There are very few studies done in the past highlighting the approach of patients with acute febrile illness without any localizing signs and symptoms. Objectives: The aim of the study was to formulate a targeted approach for evaluation and treatment of patients with acute undifferentiated febrile illness withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…During an outbreak in Sierra Leone in 2019, Proesmans et al Reported that dengue virus (DENV) infection accounted for 5% of acute fever etiologies and acute chikungunya virus infection for 39% [4]. In New York in 2020, Subramanyam et al reported that acute fever represented 15% of complaints in the elderly and around 5% in young people in the emergency room [5]. In Asia in 2014, Susilawati et al reported that the causes of acute fever are undiagnosed in 8% of cases [6].…”
Section: Introductionmentioning
confidence: 99%
“…During an outbreak in Sierra Leone in 2019, Proesmans et al Reported that dengue virus (DENV) infection accounted for 5% of acute fever etiologies and acute chikungunya virus infection for 39% [4]. In New York in 2020, Subramanyam et al reported that acute fever represented 15% of complaints in the elderly and around 5% in young people in the emergency room [5]. In Asia in 2014, Susilawati et al reported that the causes of acute fever are undiagnosed in 8% of cases [6].…”
Section: Introductionmentioning
confidence: 99%